2003
DOI: 10.1111/1467-8489.00202
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the adoption of organic horticultural technology in the UK using Duration Analysis

Abstract: Duration Analysis, which allows the timing of an event to be explored in a dynamic framework, is used to model the adoption of organic horticultural technology in the UK. The influence of a range of economic and non-economic determinants is explored using discrete time models. The empirical results highlight the importance of gender, attitudes to the environment and information networks, as well as systematic effects that influence the adoption decision over the lifetime of the producer and over the survey per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
138
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(174 citation statements)
references
References 32 publications
(30 reference statements)
19
138
1
13
Order By: Relevance
“…Within economics, unemployment duration and the duration of strikes have often been examined via duration models, such as Kennan's (1985) and Jaggia's (1991) analyses of strike duration in the US manufacturing sector. Most relevant to this study, though, is the analysis of technology adoption, such as that by Dadi et al (2004), Fuglie and Kascak (2001) and Burton et al (2003), and the adoption of privatization policy analysed by Lee (2003). As argued by Burton et al (2003) duration analysis has strengths compared with the conventional bivariate approaches.…”
Section: Duration Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Within economics, unemployment duration and the duration of strikes have often been examined via duration models, such as Kennan's (1985) and Jaggia's (1991) analyses of strike duration in the US manufacturing sector. Most relevant to this study, though, is the analysis of technology adoption, such as that by Dadi et al (2004), Fuglie and Kascak (2001) and Burton et al (2003), and the adoption of privatization policy analysed by Lee (2003). As argued by Burton et al (2003) duration analysis has strengths compared with the conventional bivariate approaches.…”
Section: Duration Analysismentioning
confidence: 99%
“…Most relevant to this study, though, is the analysis of technology adoption, such as that by Dadi et al (2004), Fuglie and Kascak (2001) and Burton et al (2003), and the adoption of privatization policy analysed by Lee (2003). As argued by Burton et al (2003) duration analysis has strengths compared with the conventional bivariate approaches. Conventional discrete choice models, such as logit or probit, cannot capture the intertemporal nature of the adoption process.…”
Section: Duration Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…I also disregarded the environmental sustainability of the new cultivation patterns, which is clearly an important criterion ( [26,27,47]). Governmental agencies should therefore evaluate the potential impacts of the alternative cultivation patterns by means of agronomic and ecological studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, I did not consider age, since it turned out to be insignificant: 59% of respondents were aged between 40 and 60. Moreover, the small sample size suggested that it was necessary to include all dummy variables as independent variables in order to increase the variability ( [26]). Finally, to obtain a more robust estimate of the variance value, I applied the Huber-White sandwich estimator with the type of tenancy as the clustering variable (since tenancy characterizes farmers more significantly than their village of residence due to the agronomic homogeneity of the area) to allow observations that were not independent within clusters (although they must be independent between clusters).…”
Section: The Econometric Analysismentioning
confidence: 99%